EUPHEMISM OF POLITICAL NEWS IN REPUBLIKA ONLINE MASS MEDIA - Yuliana Ridwan; Sri Minda Murni; Didik Santoso (Universitas Negeri Medan, 2020)
This research deals with euphemism which is found in political news in Republika mass media. The objectives of this were: (1) to investigate the types of euphemism used in political news in online mass media, (2) to describe the realization of euphemism in political news in mass media and (3) to explain the reason for realization of euphemism in political news in mass media. The research design of this study was descriptive qualitative research where the researcher explained the result of research by describing the data gained. There were 26 news with different titles with 54 euphemism. There were ten types of euphemism found in political news in Republika online mass media, namely indirection 31.4 %, abstraction 12.9 %, agreement 11.1%, remodeling 9.2%, semantic shift 9.2%, emotive 7.4%, understatement 5.5%, widening 5.5%, borrowing 3.7%, circumlocution 3.7%. Furthermore there were four ways of euphemism realized namely, implicit, explicit, direct, and indirect. Then there were five reasons using the euphemism found in political news in Republika, namely to cohesive, to protective, to underhand, to uplifting, and to ludic. The most reason using euphemism is to cohesive.Keywords: Euphemism, Political News, Republika Mass Media